2011
DOI: 10.1111/j.1744-7402.2010.02534.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bio-Nanocomposites Composed of Hydroxyapatite Reinforced with TiO2 Electrospun Nanofiber Consolidated Using High-Frequency Induction Heating

Abstract: Titanium dioxide (TiO2) nanofibers prepared by the electrospinning technique have been used as reinforcement to improve the fracture toughness of hydroxyapatite (HAp). The required TiO2 nanofibers with diameters of 50–400 nm were first prepared by the calcining and presintering of as‐prepared electrospun nanofibers of polyvinyl acetate (PVac)/titania composite at different temperatures. The composite consisting of HAp and 5 wt% of electrospun TiO2 nanofibers was then sintered at 1050° C by the high‐frequency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The fracture toughness (K IC ) of dense HAp was remarkably lower than that of human bone. [5][6][7] Unfortunately, most of these reinforcements are bioinert and/or nonbiocompatible, which remarkably decreases the bioactivity and biocompatibility of HAp-based materials, and should be avoided. 2,3 Therefore, there is a need to increase the mechanical properties, especially the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture toughness (K IC ) of dense HAp was remarkably lower than that of human bone. [5][6][7] Unfortunately, most of these reinforcements are bioinert and/or nonbiocompatible, which remarkably decreases the bioactivity and biocompatibility of HAp-based materials, and should be avoided. 2,3 Therefore, there is a need to increase the mechanical properties, especially the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the poor mechanical properties, especially the low toughness of HAp bioceramics have severely hindered their clinical applications, such as artificial bones or teeth. 5,6 The secondary phases of band a-TCP from HAp decomposition are degradable and will ultimately decrease the mechanical properties of the implants during the degradation. Several attempts had been applied to solve this problem, such as using glass as the liquid phase sintering additives to improve mechanical strength, 4 using ZrO 2 , TiO 2 , metals, and carbon nanotubes etc.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis involves the following four steps: (1) the preparation of the titania precursor sol, (2) mixing of the sol with the polymer template to obtain the solution for electrospinning, (3) electrospinning of the solution with the use of the apparatus showed in Figure 4, and (4) the calcination of as-prepared TNF to obtain crystalline titania nanofibers [164]. The morphology and the diameter of the electrospun titania depend on the following parameters related to: (a) the solution, (b) the process, and (c) the ambient ( Table 2), while the structure of formed nanofibers is strictly associated with the postcalcination process [165][166][167][168][169][170][171][172][173]. Another technique to produce titania nanofibrous coatings is the laser ablation, proposed by Tavangar et al [174].…”
Section: Titania Nanofibrous Coatings (Tnfs)mentioning
confidence: 99%
“…Calcination temperature Higher temperature results in the reduction of nanofiber size, because of the loss of polymer and the crystallization process of titania [165,168,[171][172][173] Table 2. Summarization of the electrospinning parameters affected the nanofibers morphology.…”
Section: Ambient Parametersmentioning
confidence: 99%
“…2 So, it is only used in nonload areas of the human body such as the ossicles in the middle ear. [16][17][18] Fidancevska et al have shown that composite with 15% TiO 2 content improves mechanical properties. Several works have consequently been carried out on structural modifications and mechanical properties of HA in the presence of oxides or metallic dispersions used as reinforcing agents.…”
Section: Introductionmentioning
confidence: 99%